Comparison of phytoplankton control measures in reducing cyanobacteria assemblage of reservoirs found in the arid region of Southern Africa. (23rd April 2021) - Sirunda, Johannes; Oberholster, Paul; Wolfaardt, Gideon; Botes, Marelize; Truter, Christoff
Abstract: Ecological restorations of reservoirs are implemented worldwide; however, minimal successes are reported and understood for warmer African lakes like Swakoppoort Dam, Namibia. The objectives of the study were (a) to establish the effectiveness of the two control measures in reducing cyanobacteria growths in comparison with untreated control areas and (b) to compare the results generated before and after control measures with the reference Von Bach Dam. During Phoslock ® treatment, the average cyanobacteria cells and total phosphate (TP) were 90, 521 cells/ml and 0.3 mg/L in the treated area and 55, 338 cells/ml and 0.1 mg/L in the control area. During Solar Powered Circulation (SPC) treatment, the average cyanobacteria cells were on average 906, 420 cells/ml in the treated areas and 121, 891 cells/ml in the control area. The TP on average was 0.3 mg/L during SPC treatment, while during the combined treatment, the average cyanobacteria cells, TP, and total nitrogen (TN) were 18, 387, 226 cells/ml, 0.27 mg/L, and 2.41 mg/L before and 22, 836, 511 cells/ml, 0.42 mg/L, and 1.50 mg/L after treatment. This was higher compared to the reference site. PCA triplot indicates no grouping pattern, and the repeated‐measures mixed model analyses indicate that treatment had no significant effect on cyanobacteria cells. It was evident that the two control measures were ineffective in reducing cyanobacterial cells. Practitioner points: Key findings of the article: Two phytoplankton control measures were found ineffective to reduce the cyanobacterial cell numbers. High cell numbers of cyanobacteria were recorded at the treatment areas compared to untreated control areas during both treatments. The combined effect of the two control measures was ineffective as more cyanobacterial cells were recorded during the treatment. During control measure treatment, the Swakoppoort Dam was hypertrophic, which could be due to a malfunctioned WWTP upstream. The inefficiency of the control measures could be due to small treatment area, higher nutrients, or treatment period. The implications of the results to water/wastewater practice: The selection of appropriate mitigation measures considering treatment area for dams with high nutrient situated in warmer arid environments. There is a need to understand the trophic relationships, climatic conditions, and the sources of the internal and external nutrients to manage water quality. Focus on point and non‐point sources of nutrients as the root causes of the degradation of Swakoppoort Dam water. Abstract : (a)Phoslock ® treatment results at the treated area (SP1) compared to untreated control area (SP2) in the Swakoppoort Dam. (b)Solar Powered Circulation (SPCs) treatment results at the treated area (SP1, 2, 3, 4, 5, & 6) compared untreated control area (Ctrl) in the Swakoppoort Dam. (c)The combined effect of the two phytoplankton control measures (Phoslock ® and Solar Powered Circulation (SPCs) treatment) results before and after control measures in the Swakoppoort Dam.